Pugs of the frozen north - Reeve, Philip; McIntyre, Sarah (New York : Random House, 2016)
New friends Sika and Shen try to beat the odds and win the Great Northern Race--in a sled pulled by a team of sixty-six pugs--in hopes of meeting the Snowfather and having him grant their wish.
"Originally published in hardcover by Oxford University Press, Oxford, in 2015."
Keywords: Adventure and adventurers -- Fiction; Sled dog racing -- Fiction; Pug -- Fiction; Dogs -- Fiction; Magic -- Fiction; Arctic regions -- Fiction